Preliminary survey of the distribution of shelled mollusks at Taklong, Guimaras Island - Jaranilla, Ruben J.
This paper attempted to study the distribution of shelled mollusks in Taklong Island, Guimaras, Iloilo. It specifically attempted to investigate the effects of the substratum on the distribution of shelled mollusks. The study is significant because it provides a baseline information on the kind of shelled mollusks found in the littoral zone of Taklong waters. Also it will establish a relationship between the kind of mollusks and the type of substratum where they are found. It can also be used as a springboard for further studies along related areas. The study was limited only to the shelled mollusks fauna found in the littoral area of Taklong Island. The study was conducted over a three-month period starting from October to December, 1980. Observations were done during the low tides only. Three stations were studied using the line transect method. Ten transects at five-meter intervals were constructed with half of each transect submerged and the other half exposed. The shelled molluscan fauna found within a ten-centimeter line to the right and to the left of each line transect was then counted. Species and number were recorded as well as location in the transect. Shelled mollusks were then identified up to the genus level. Two reasons governed the selection of the study stations, namely : width of littoral area and accessibility of the study areas from SitioLusaran. Data gathered from the three study stations revealed that the distribution of shelled mollusks was dependent on the nature of the substratum. Thus sessile organisms preferred rocky substrata to which they can cling. In the light of these findings, a twelve-month period is being recommended for observation and study of shelled mollusks distribution. As a basis for comparison, a more extensive area of study is also being recommended. Lastly, other factors that may affect the distribution of shelled mollusks be investigated also. Finally, this study has educational implications. Biology teachers can employ the line transect method to map out populations in a particular area in the field.